415 OCCUPATIONAL PHYSICAL ACTIVITY AND THE RISK OF GORD, BARRETT'S OESOPHAGUS AND OESOPHAGEAL ADENOCARCINOMA A PROSPECTIVE COHORT STUDY IN UK BIOBANK. (14th September 2020) - Lam, S; Savva, G; Alexandre, L; Kumar, B; Hart, A
Abstract:  : Recreational physical activity has been shown to protect against the development of oesophageal adenocarcinoma as well as gastroesophageal reflux disease (GORD), but such effects have not been demonstrated for non-recreational activity. We examined whether high levels of occupational physical activity (heavy manual labour or physical work) were associated with the risk of oesophageal adenocarcinoma as well as its sequential precursor diseases; gastroesophageal reflux disease (GORD), reflux oesophagitis and Barrett's oesophagus. Methods: In this population-based prospective cohort study, participants aged between 37 to 73 years were recruited from 22 regions across the United Kingdom. Baseline occupational information of job type and levels of heavy manual activity was assessed using both questionnaires and verbal interviews. Incident cases were identified by linkage with routinely collected hospital inpatient and cancer registry data for England, Scotland and Wales. Primary clinical outcomes were GORD without oesophagitis, GORD with oesophagitis (reflux oesophagitis), Barrett's oesophagus and oesophageal adenocarcinoma. The effects of heavy manual activity on disease risk were estimated using Cox proportional hazard regression. Results: Between 2006 and 2010, 502 524 men and women were enrolled. Main analyses were limited to the working population with a full set of variables of interest (n = 266 453). Compared to jobs with low levels of heavy manual activity, high level jobs had increased hazard ratios (HRs) for GORD (1.20, 95% CI 1.11–1.30), reflux oesophagitis (1.17, 95% CI 1.04–1.31) and Barrett's oesophagus (1.13, 95% CI 0.98–1.32), but not oesophageal adenocarcinoma (0.91 95% CI 0.54–1.56). Conclusion: High levels of occupational heavy manual activity could be used as a risk factor for GORD and reflux oesophagitis, the precursor diseases of Barrett's oesophagus and oesophageal adenocarcinoma.